CONCEPTION RATE IN EARLY POSTPARTUM DAIRY COWS TREATED WITH OVSYNCH + FTAI - KANTHARAJ, S; HEMALATHA, H; MURUGAVEL, K; ANTOINE, D (The Indian Journal of Animal Reproduction, 2023)
A total of 18 early postpartum dairy cows were randomly divided into two groups and Group-I cows (n=9) weresubjected to AI at observed estrus and Group-II cows (n=9) were subjected to Ovsynch protocol with Fixed TimeArtificial Insemination (FTAI). The conception rate in Group-I and II was 22.22 and 44.44 %, respectively. Thoughthere was no significant difference in the conception rate between the two groups, cows subjected to Ovsynch had anappreciable conception rate.
Keywords: Postpartum Dairy Cows; Ovsynch; FTAI; Conception rate